KAJIAN PSIKOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER NOVEL RANTAU 1 MUARA KARYA AHMAD FUADI SERTA RELEVANSINYA SEBAGAI MATERI AJAR APRESIASI SASTRA DI SMA - Nisa’ A’fifatul Azizah; Herman J Waluyo; Chafit Ulya (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to describe and explain (1) the intrinsic element of novel Rantau 1 Muara by Ahmad Fuadi, (2) the emotional condition of the character depicted in the novel Rantau 1 Muara by Ahmad Fuadi according to Sigmund Freud’s theory, (3) the values of character education contained in the novel Rantau 1 Muara by Ahmad Fuadi, (4) the relevancy of novel Rantau 1 Muara by Ahmad Fuadi as a teaching material for literary appreciation class in Senior High School level. This study used a descriptive qualitative method with literary psychology approach. Data collection was carried out with document analysis techniques and indept interviews. The validity data test has been done using triangulation theory technique and data triangulation. The analysis of data was conducted using flow analysis i.e, the data reduction, data presentation, and conclutions determination. The results of the study are (1) the intrinsic elements that build the novel Rantau 1 Muara are theme, characterizations, plot, settings, and author’s point of view; (2) the emotional  conditions experienced by characters in the novel Rantau 1 Muara are influenced by three elements i.e, id, ego, and superego; (3) the value of character education that contained in the novel Rantau 1 Muara there are 13 values including religious, honest, tolerance, discipline, hardwork, independent, curiosity, spirit of nationality, love the country, friendly/ communicate, like reading, concern to social issue, and responsibly; (4) novel Rantau 1 Muara can be used as an alternative teaching material of literary appreciation class in Senior High School level.